The impact of sociality and affective valence on brain activation: A meta-analysis - Atzil, Shir; Satpute, Ajay B.; Zhang, Jiahe; Parrish, Michael H.; Shablack, Holly; MacCormack, Jennifer K.; Leshin, Joseph; Goel, Srishti; Brooks, Jeffrey A.; Kang, Jian; Xu, Yuliang; Cohen, Matan; et al. (NeuroImage (Orlando, Fla.), 2023)
•In humans, social stimuli are highly affective. We map how sociality and affective valence affect brain activations across the literature.•We meta-analyzed 493 neuroimaging studies of social and non-social affective paradigms published from 1992 to 2019, including 7801 participants.•Social and non-social affective stimuli are associated with overlapping activations within visceromotor control regions.•Social processing involves additional cortical activations previously associated with abstraction and prediction.•Social v. non-social affective processing does not use unique circuitry but sociality relies on relatively more elaborate cortical processing. Thirty years of neuroimaging reveal the set of brain regions consistently associated with pleasant and unpleasant affect in humans—or the neural reference space for valence. Yet some of humans’ most potent affective states occur in the context of other humans. Prior work has yet to differentiate how the neural reference space for valence varies as a product of the sociality of affective stimuli. To address this question, we meta-analyzed across 614 social and non-social affective neuroimaging contrasts, summarizing the brain regions that are consistently activated for social and non-social affective information. We demonstrate that across the literature, social and non-social affective stimuli yield overlapping activations within regions associated with visceromotor control, including the amygdala, hypothalamus, anterior cingulate cortex and insula. However, we find that social processing differs from non-social affective processing in that it involves additional cortical activations in the medial prefrontal and posterior cingulum that have been associated with mentalizing and prediction. A Bayesian classifier was able to differentiate unpleasant from pleasant affect, but not social from non-social affective states. Moreover, it was not able to classify unpleasantness from pleasantness at the highest levels of sociality. These findings suggest that highly social scenarios may be equally salient to humans, regardless of their valence.